ANALISIS PERENCANAAN PENGELOLAAN GEOPARK (TAMAN BUMI) GOA BATU KAPAL KECAMATAN SANGIR KABUPATEN SOLOK SELATAN - Osronita Osronita; Novelisa Suryani; Hary Febrianto; Fajri Fajri (Universitas Tamansiswa Padang, 2023)
The karst area is one of the important potentials in terms of socio-economic and scientific, even has a hydrological function (water system) which is very important in supporting the survival of living things on it. Karst is a landscape that is very vulnerable to natural and human pressures. Batu Kapal Cave is a unique karst that is designated as one of the Geoheritage of West Sumatra. This study aims to analyze the management planning of Goa Batu Kapal Geopark, Sangir District, South Solok Regency. The type of research used is exploratory descriptive with the Grounded theory method, which is a research methodology where field data is the source of theory formulation. The development and management of Batu Kapal Cave Karst Area can be used for geotourism. Various activities carried out include Caving Campgrounds, Rock Climbing, Playgrounds, Hammock Camping, Museums, Honey Bee Farming, location of Research and Education. The concept of management with community-based tourism and the use of selected local natural materials for the development of supporting facilities.